2019
DOI: 10.1039/c9nr03853a
|View full text |Cite
|
Sign up to set email alerts
|

Chirality manifestation in elastic coupling between the layers of double-walled carbon nanotubes

Abstract: Most likely, both layers in double-walled carbon nanotubes have the same handedness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 76 publications
0
21
0
2
Order By: Relevance
“…Consequently, heterohelical combinations of (P)/(M) and (M)/(P) were preferred over homohelical combinations of (P)/(P) and (M)/(M), and an enthalpic origin for the discrimination was quantitatively disclosed. This result may prompt reconsiderations of previous proposals of homohelical preferences for infinite i-DWNTs [29][30][31] . Spectral changes were noted upon formation of the i-DWNT complex ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Consequently, heterohelical combinations of (P)/(M) and (M)/(P) were preferred over homohelical combinations of (P)/(P) and (M)/(M), and an enthalpic origin for the discrimination was quantitatively disclosed. This result may prompt reconsiderations of previous proposals of homohelical preferences for infinite i-DWNTs [29][30][31] . Spectral changes were noted upon formation of the i-DWNT complex ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 87%
“…The ITC result was also important to clarify that the enthalpic difference (ΔΔH) of incommensurate carbon bilayers with diastereomeric orientations can be as large as 1 kcal mol −1 even for short, finite cylindrical molecules. In previous studies of infinite i-DWNTs with transmission electron microscopy, tomographic analyses led to the proposal that homohelical CNT combinations were energetically preferred over heterohelical combinations 29,30 . This previous proposal contradicts the present quantitative thermodynamic data of i-DWNT segments, and two explanations might be possible: (1) the stereoselectivity of i-DWNT formation may be kinetically determined, which may prefer homohelical combinations, and (2) the proposal made for the 16 i-DWNT specimens was not statistically sufficient.…”
Section: Stereoselective Spontaneous Assembly Of the I-dwnt Complexmentioning
confidence: 99%
“…Another problem was raised in 2017 by Ghedjatti et al, who hypothesized that the formation of specific DWCNTs with Δθ ≈ 0° and Δθ > 25° (regions I and II in Figure 2c, respectively) is forbidden due to the mechanical vdW coupling. [25] However, later independent studies by He et al [43] and Rochal et al [42] demonstrated that these geometrical configurations do exist.…”
Section: And the Interlayer Twist Anglementioning
confidence: 99%
“…The latter corresponds to any inner-outer SWCNT pairs falling within an outer dia meter range of 1.0 < D out < 5.0 nm and an interlayer distance range of 0.30 < Δr < 0.40 nm (blue bars and colored dots in Figures 2b,c, respectively), where the ranges of D out and Δr correspond to the limits of the experimental distributions. [42] The interlayer distance Δr in naturally grown DWCNTs is distributed mainly between 0.30 and 0.40 nm with a peak value at around 0.34-0.35 nm (Figure 2b, top panel). It contrasts with the constant Δr distribution for the set of all geometrically possible DWCNT combinations (blue bars in Figure 2b).…”
Section: And the Interlayer Twist Anglementioning
confidence: 99%
See 1 more Smart Citation